أثر التماثل التنظيمي بوصفه متغيرا وسيطًا في العلاقة بين الرضا الوظيفي والالتزام التنظيمي لدى معلمي مدارس التعليم الأساسي في سلطنة عمان - شهومي، سعيد بن راشد بن علي (Kulliyah of Education, International Islamic University Malaysia, 2020)
Educational institutions play a significant role that has a great impact in society's development and teachers undoubtedly represent the cornerstone of the educational process. This vital role teachers play in educational process calls for taking care of teachers so that they can perform their job well. Based on social exchange theory and social identity theory, this research examines the mediating role of organizational identification in the relationship between job satisfaction and organizational commitment from teachers' perspective. In this study, the researcher adopted the descriptive survey method, which is an appropriate approach suits the objectives of this study. Based on the nature of this quantitative study, the researcher used the cross-sectional method to collect its data. A questionnaire of 92 items was distributed randomly to the sample of this study (1,000 teachers) in seven educational governorates. Out of the distributed 1000 questionnaires, 846 (419 males and 427 females) were returned and valid for analysis. SPSS software (version 24) was used for the preliminary descriptive analysis, while AMOS software (Version 24) was employed for the main inferential analysis, namely Structure Equation Modelling (SEM). SEM via AMOS was conducted in two main steps, namely the measurement model to assess the data's validity and reliability, while the structural modeling was conducted to examine they hypothesized relationships between the variables. The results revealed a direct impact of job satisfaction on organizational identification and indirect effect on organizational commitment through organizational identification. The results were discussed in the light of the theoretical framework and previous studies. The study concluded with practical recommendations for Ministry of Education in Oman as well as some theoretical recommendations for future studies.